RELIGIUSITAS DAN PERILAKU DISIPLIN SANTRIWATI MADRASAH ALIYAH PONDOK PESANTREN - Khotimah, Khusnul (Jurnal Studia Insania, 2019)
The purpose of the study was to prove relationship religiosity to discipline behavior in a student at Islamic boarding schools. Student noncompliance with regulation indicates a lack of disciplinary behavior. So student needs to increase the value of religiosity in Islamic boarding school as a behavior controllers, one of which disciplined behavior. Correlational research type with a quantitative approach. Sample populations of student class XI and using random sampling with 68 samples. Research data collected using the religiosity scale and discipline behavior consisting of 26 and 27 items valid with a reliability coefficient of 0,700 and 0,787. The result of the study indicates that there is a positive relationship between religiosity and the behavior of student discipline, which means the higher the religiosity, the more positive the discipline behavior with the correlation coefficient rxy=0,328; p=0,000 (p<0,01). R square obtained by 0,108, meaning that religiosity effectively contributes to 10,8% for discipline behavior.